Maxim Analysis of Politeness In Video Interview with IMF Managing Director After G20 Summit in Bali 2022 - Ima Nurhasanah; Myrna Laksman (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to provide a comprehensive understanding of how the principles of politeness influence interactions in formal contexts, particularly in video interviews featuring the IMF Managing Director after the 2022 G20 Summit in Bali. The research objective is to investigate the extent to which interview participants adhere to or violate politeness principles in their communication, focusing on the use of politeness maxims and strategies. A pragmatic approach is employed to analyze the interview transcript, yielding deeper insights into the interaction. The analysis reveals that interview participants actively employ various politeness strategies to maintain harmonious interpersonal relations while effectively communicating important policy and economic messages. However, instances of politeness maxim violations also occur, potentially influenced by communicative goals or cultural differences. This study highlights the importance of politeness in formal interaction contexts such as video interviews, as well as the complexity of balancing politeness with communication effectiveness. The implications of these findings are not only relevant for understanding politeness practices in video interviews but also for intercultural communication more broadly. Further research in this field is expected to provide deeper insights into politeness practices and effective communication strategies in formal contexts.